Association of Helicobacter Pylori Infection and Ectopic Pregnancy - Fariba NanBakhsh; Tahereh Behrouzy Lak; Mahsa Tabean; Sima Oshnouei; Pooya Mazlumi (Tehran University of Medical Sciences, 2016)
Objective: To evaluate the importance of cytokine type in embryo implantation in uterus specified and activated macrophages interfere the tube movements and embryo retention in uterine tubes by smooth muscle relaxation and disrupting ciliary function. Therefore, increased risk of infection with HP during pregnancy, we investigated relation between Helicobacter pylori (HP) infection and prevalence of ectopic pregnancy (EP) in this study. Materials and methods: This is cross-sectional study from March 2012 to May 2013. Totally 207 women were enrolled randomly from which 101 had EP (Case group) and 106 were selected as control group with normal pregnancy. A 2-cc blood sample was taken from each patient to evaluate the specific IgG titer by ELISA method. All results of samples with positive H. pylori IgG were assayed for anti-CagA, IgG antibodies. A questionnaire was filled for each subject. The associations between CagA positive cases with odds of Ectopic pregnancy incidence were analyzed by using SPSS software, ver. 19 (Chicago, IL, USA). Results: Mean (± SD) of age were 21.0 ± 5.78 and 30.78 ± 5.10 years for cases and controls group respectively. These groups didn't show any significance difference in age and parity.H. pylori IgG antibodies were positive among 99 and 103 (98.2% vs. 97.2%) in women with EP and normal pregnancy respectively. Relationship between IgG status and EP was not significant (OR = 1.31: 95% CI = 0.7-2.52, Pvalue = 0.37). In particular anti-CagA antibodies were positive among 45 and 39(45.92% vs. 36.97%) in women with EP and normal pregnancy respectively. Among women with CagA positive strains had higher odds of Ep (OR = 1.46: 95% CI = 0.8-2.65, Pvalue = 0.18), but it wasn't significant. Conclusion: According to the result of this study there was not any association between HP infection and Ectopic pregnancy. We recommend more studies with larger sample size for determining the effect of CagA positive strains on EP.